Estuarine ecohydrology - Wolanski, Eric; Elliott, M. (Michael) (Elsevier Science, 2015)
Estuarine Ecohydrology, Second Edition, provides an ecohydrology viewpoint of an estuary as an ecosystem by focusing on its principal components, the river, the estuarine waters, the sediment, the nutrients, the wetlands, the oceanic influence, and the aquatic food web, as well as models of the health of an estuary ecosystem. Estuaries, the intersection of freshwater and coastal ecosystems, exhibit complex physical and biological processes which must be understood in order to sustain and restore them when necessary. This book demonstrates how, based on an understanding of the processes controlling estuarine ecosystem health, one can quantify its ability to cope with human stresses. The theories, models, and real-world solutions presented serve as a toolkit for designing a management plan for the ecologically sustainable development of estuaries.--Provided by publisher.